Pelatihan Parenting dalam Mewujudkan Keluarga Sakinah Mawaddah Warahmah - Nurul Fadhillah Arna; Harmilawati Harmilawati (Jumat Keagamaan: Jurnal Pengabdian Masyarakat, 2022)
The implementation of the activities uses the participatory action research (PAR) method. The goal is to improve the skills of parents in carrying out care and upbringing in their own families and explain to parents about the process of good child education. As for the object of the real professional work course (KKNP) for the author for 2 months, namely parents. In parenting training activities in realizing a sakinah mawaddah mawahmah family in Desa Bulu Tanah, Kec. Kajuara, Kab. Bone. Parenting training is held once during KKN-P. The place is located in the Fastabiqul Khairat Mosque in Dusun Cangkano.